HUBUNGAN POLA MAKAN DENGAN STATUS GIZI ANAK SEKOLAH DASAR NEGERI 004 SEKUPANG KOTA BATAM - Afif D Alba; Dedy Siska (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Nutritional status is an expression of a state of balance in the form of certain variables, or the manifestation of nutrients in the form of certain variables. (Hartini, 2018). The 2018 Health Profile of the Republic of Indonesia states that the percentage of malnutrition in toddlers aged 0-59 months in Indonesia is 3.9%, while the percentage of undernutrition is 13.8%. In the Riau Islands, toddlers with malnutrition problems are 3.2%, while undernutrition is 9.8% (Ministry of Health of the Republic of Indonesia, 2018). Factors that influence nutritional status are inadequate nutritional intake, health, and diet. The purpose of this study was to determine the relationship between diet and nutritional status of elementary school children in Sekupang 004. The design of this study was observational with a cross-sectional design. The population in this study were all students of Sekupang 004 Elementary School, Batam City, with a sample using simple random sampling of 63 respondents. The results of the study conducted Kolmogorov Test parenting patterns with nutritional status obtained P value 0.000 <α 0.05, and diet patterns with nutritional status obtained P value 0.000 <α 0.05. The conclusion of this study is that there is a relationship between parenting patterns and nutritional status, there is a relationship between diet patterns and nutritional status in students. This study can be a consideration in making policies for implementing good parenting patterns and providing education on diet and nutritional status.